Mef2d acts upstream of muscle identity genes and couples lateral myogenesis to dermomyotome formation in Xenopus laevis. - Bruno Della Gaspera (Public Library of Science (PLoS), 2012)
Xenopus myotome is formed by a first medial and lateral myogenesis directly arising from the presomitic mesoderm followed by a second myogenic wave emanating from the dermomyotome. Here, by a series of gain and loss of function experiments, we showed that Mef2d, a member of the Mef2 family of MADS-box transcription factors, appeared as an upstream regulator of lateral myogenesis, and as an inducer of dermomyotome formation at the beginning of neurulation. In the lateral presomitic cells, we showed that Mef2d transactivates Myod expression which is necessary for lateral myogenesis. In the most lateral cells of the presomitic mesoderm, we showed that Mef2d and Paraxis (Tcf15), a member of the Twist family of transcription factors, were co-localized and activate directly the expression of Meox2, which acts upstream of Pax3 expression during dermomyotome formation. Cell tracing experiments confirm that the most lateral Meox2 expressing cells of the presomitic mesoderm correspond to the dermomyotome progenitors since they give rise to the most dorsal cells of the somitic mesoderm. Thus, Xenopus Mef2d couples lateral myogenesis to dermomyotome formation before somite segmentation. These results together with our previous works reveal striking similarities between dermomyotome and tendon formation in Xenopus: both develop in association with myogenic cells and both involve a gene transactivation pathway where one member of the Mef2 family, Mef2d or Mef2c, cooperates with a bHLH protein of the Twist family, Paraxis or Scx (Scleraxis) respectively. We propose that these shared characteristics in Xenopus laevis reflect the existence of a vertebrate ancestral mechanism which has coupled the development of the myogenic cells to the formation of associated tissues during somite compartmentalization.